Belatacept: a novel immunosuppressive agent for kidney transplant recipients. (November 2012) - Charpentier, Bernard
Long-term graft and patient survival remain the most significant challenges in kidney transplantation, and new therapies are needed to improve long-term outcomes. Belatacept, a first-in-class selective costimulation blocker, has been approved for prophylaxis of organ rejection in kidney transplant recipients who are positive for EBV. In Phase III trials, belatacept demonstrated superior preservation of renal function and comparable patient/graft survival compared with cyclosporine, while avoiding the renal toxicities and other adverse events associated with the use of a calcineurin inhibitor. Patients treated with belatacept had higher rates of acute rejection than cyclosporine-treated patients. However, acute rejection episodes that occurred early and did not recur were generally not associated with donor-specific antibodies, and few belatacept patients had graft loss due to rejection. The improved renal benefit with belatacept may translate into improvements in long-term graft and patient outcomes. Targeting T-cell costimulation is an important new option for maintenance immunosuppression in kidney transplant recipients.